ARCHER – e-Research Tools for Research Data Management - Steve Androulakis; Ashley M. Buckle; Ian Atkinson; David Groenewegen; Nick Nicholas; Andrew Treloar; Anthony Beitz (International Journal of Digital Curation, 2009)
With new scientific instruments growing exponentially in their capability to generate research data, new infrastructure needs to be developed and deployed to allow researchers to effectively and securely manage their research data from collection, publication, and eventual dissemination to research communities. In particular, researchers need to be able to easily acquire data from instruments, store and manage potentially large quantities of data, easily process the data, share research resources and work spaces with colleagues both inside and outside of their institution, search and discover across their accessible collections, and easily publish datasets and related research artefacts. The ARCHER Project has developed production-ready generic e-Research infrastructure including: a Research Repository; Scientific Dataset Managers (both a web and desktop application); Distributed Integrated Multi-Sensor and Instrument Middleware; and a Collaborative Workspace Environment. Institutions can selectively deploy these components to greatly assist their researchers in managing their research data.